ANALISA PREDIKSI PENGGUNAAN MOBILE APPLICATION UNTUK STARTUP MONTIRKELILING.COM DENGAN METODE MARKOV CHAIN - Sutabri, Tata; Dinata, Aria; Majduddin, Majduddin; Agustriani, Nyimas Hamidah Purnama (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
The research uses both qualitative and quantitative approaches, as well as interviews and questionnaires as data collection tools. The aim of this study is to determine the number of users of the Montirkeliling.com application and to project the likelihood of changes in the application's usage. In the study of the Analysis of Mobile Application Usage Prediction for the startup Montirkeliling.com, the Markov Chain method is employed. In the context of Montirkeliling.com application usage, the Markov Chain method is used to calculate and predict changes in the number of application users over time based on past usage patterns. This method allows for modeling transitions between different states or conditions, thereby aiding in understanding and probabilistically predicting user behavior. The research provides valuable insights for decision-makers regarding the use of the Montirkeliling.com application. The analysis of the data shows a change in the application's usage, initially relatively high but continuously decreasing, with an increase projected in the following years.